Funding Conservation Locally: Insights from Behavioral Experiments in Indonesia. Issue 2 (29th June 2017) - Nelson, Katherine M.; Schlüter, Achim; Vance, Colin
Abstract: Proximate stressors such as destructive fishing are key drivers of coral reef degradation. Conservation strategies that marshal local action and are tailored to the preferences of the target group are thus needed to sustain coral resources. We experimentally analyze the behavior of marine resource users in a coastal village in Indonesia to gain insight into whether people prefer to donate time or money to environmental or other charitable causes. Each person is subject to one of four treatments: monetary donation, monetary donation match, volunteer time donation, and volunteer time donation match. Contrasting with the existing literature, we find that participants give significantly more when donating money compared to time. We also find that matching donations increases the percent of people giving but does not increase the amount donated. This research furthers our understanding of what motivates resource users in a developing country to contribute to the provision of public goods.